2016
DOI: 10.1186/s12929-016-0234-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface vimentin is critical for the cell entry of SARS-CoV

Abstract: BackgroundSevere acute respiratory syndrome coronavirus (SARS-CoV) caused a global panic due to its high morbidity and mortality during 2002 and 2003. Soon after the deadly disease outbreak, the angiotensin-converting enzyme 2 (ACE2) was identified as a functional cellular receptor in vitro and in vivo for SARS-CoV spike protein. However, ACE2 solely is not sufficient to allow host cells to become susceptible to SARS-CoV infection, and other host factors may be involved in SARS-CoV spike protein-ACE2 complex.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
162
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(163 citation statements)
references
References 42 publications
0
162
0
Order By: Relevance
“…Secreted vimentin could also be detected in vitro in astrocyte-conditioned medium (Greco, Seeholzer, Mak, Spruce, & Ischiropoulos, 2010) and has been described for other cell types like macrophages and neutrophils (Moisan & Girard, 2006;Mor-Vaknin, Punturieri, Sitwala, & Markovitz, 2003). Functionally, extracellular vimentin is involved in binding to bacterial or viral pathogens (Ghosh et al, 2018;Yu et al, 2016). In the context of astrocyte-neuron interactions, it was shown that C-terminal residues of secreted vimentin can bind to the neuronal insulin-like growth factor 1 receptor, thereby stimulating its phosphorylation and axonal outgrowth of cultured neocortical neurons (Shigyo, Kuboyama, Sawai, Tada-Umezaki, & Tohda, 2015).…”
mentioning
confidence: 88%
“…Secreted vimentin could also be detected in vitro in astrocyte-conditioned medium (Greco, Seeholzer, Mak, Spruce, & Ischiropoulos, 2010) and has been described for other cell types like macrophages and neutrophils (Moisan & Girard, 2006;Mor-Vaknin, Punturieri, Sitwala, & Markovitz, 2003). Functionally, extracellular vimentin is involved in binding to bacterial or viral pathogens (Ghosh et al, 2018;Yu et al, 2016). In the context of astrocyte-neuron interactions, it was shown that C-terminal residues of secreted vimentin can bind to the neuronal insulin-like growth factor 1 receptor, thereby stimulating its phosphorylation and axonal outgrowth of cultured neocortical neurons (Shigyo, Kuboyama, Sawai, Tada-Umezaki, & Tohda, 2015).…”
mentioning
confidence: 88%
“…Moreover, VP1 caused the vimentin rearrangement in astrocyte cells, facilitating virus infection in the CNS (Haolong et al 2013). In the consideration that endothelial cells, vimentin is utilized by various viruses, including at least cowpea mosaic virus (Koudelka et al 2009), dengue virus (Yang et al 2016), and severe acute respiratory syndrome coronavirus (Yu et al 2016), we speculated that VP1 may exploit endothelial cells and vimentin. In the accordance with the above speculation, VP1 activated TGF-β/Smad-3/NF-κB pathways, leading to the increased expression of vimentin in brain endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin is part of a cytoskeleton structure that has the role of a receptor for virus entering the cell, especially as a viral receptor or attachment receptor. For example, the direct interaction between vimentin and SARS-CoV spike protein during viral entry and as the virus enters the receptor (Yu et al, 2016). Cell surface vimentin is an attachment receptor for enterovirus 7 and increases the infectivity of EV71 (Du et al, 2014).…”
Section: Discussionmentioning
confidence: 99%